The influence of regional original revenue, general allocation fund, and special allocation fund on gross regional domestic product through capital expenditure in North Sulawesi Province for the 2011–2022 period - Lalimbat, Sepriani; Kumenaung, Anderson Guntur; Rorong, Ita Pingkan F. (The Contrarian : Finance, Accounting, and Business Research, 2025)
The amendment of Law Number 22 of 1999 to Law Number 32 of 2004 represents a policy initiative by the central government to grant broader autonomy to local governments, allowing them to manage their own administrative and financial affairs with minimal intervention. In this context, local governments also gain wider authority to utilize financial resources in accordance with regional needs and the aspirations of the local population. This study aims to examine the influence of Regional Original Revenue, the General Allocation Fund, and the Special Allocation Fund on Gross Regional Domestic Product, with Capital Expenditure serving as an intervening variable in the Provincial Government of North Sulawesi. The research utilizes secondary data obtained from the Regional Revenue and Expenditure Budget Realization Reports of North Sulawesi Province and the Central Bureau of Statistics for the period 2011–2022. The relationships among variables are analyzed using multiple linear regression and path analysis. The results show that Regional Original Revenue and the General Allocation Fund have a significant positive effect on Capital Expenditure, while the Special Allocation Fund has no significant effect. Regional Original Revenue also has a significant positive effect on Gross Regional Domestic Product. In contrast, the General Allocation Fund and the Special Allocation Fund have no significant effect on Gross Regional Domestic Product. Meanwhile, Capital Expenditure has a significant positive effect on Gross Regional Domestic Product.